2020
DOI: 10.1007/s13593-020-0611-1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of market-oriented research for rice production in Tanzania. A review

Abstract: Rice consumption in Tanzania has greatly increased since the 1960s; it is predicted to continue to increase owing to urbanization and changes in consumer preferences from traditional staples to rice. In this study, we review rice agroecology, its value chain, and price determinants, and the history of and challenges to rice research in Tanzania. Our main findings are as follows: (1) rice cultivation can be classified into three major categories: irrigated lowland, rainfed lowland, and rainfed upland. Irrigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 41 publications
0
14
1
5
Order By: Relevance
“…Sekiya et al [14] reported that farmers reject most new varieties because they are not yet widely accepted by consumers; however, we found that locally grown japonica rice in Nairobi was acceptable by consumers to some extent.…”
Section: Consumer Acceptabiltiy Of Locally Grown Japonica Ricecontrasting
confidence: 65%
See 2 more Smart Citations
“…Sekiya et al [14] reported that farmers reject most new varieties because they are not yet widely accepted by consumers; however, we found that locally grown japonica rice in Nairobi was acceptable by consumers to some extent.…”
Section: Consumer Acceptabiltiy Of Locally Grown Japonica Ricecontrasting
confidence: 65%
“…As the demand for locally grown japonica rice increases, the market is expected to expand and the number of relevant stakeholders in each stage will grow. An increase in the number of stakeholders in the process from the producer to the consumer is one factor that ultimately contributes to higher prices for consumers [14,[33][34][35]. According to our value chain analysis, the smaller the number of related stakeholders, the larger the net profit of each, and the greater the tendency for the value-added ratio to increase is.…”
Section: Profitability Of the Rice Value Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the rice produced in the country is under rainfed conditions. 4 There is a stiff competition with other food crops in terms of area under production because all the selected food crops grow during the long rainy season (agricultural season). As a result, all the major food crops compete for land and inputs based on these factors' variations.…”
Section: Markov Chain Analysismentioning
confidence: 99%
“…3 In Africa, rice consumption has been growing at a faster rate than any other staple food, at around 5.5% per year, due to urbanisation and related changes in eating habits, as well as population growth. 4 In Tanzania, it is the second most common cereal after maize, and it contributes to the country's food and household nutrition security. It is grown in 64 districts, affecting the livelihoods of over two million people.…”
Section: Introductionmentioning
confidence: 99%